Comparison of Voice Quality and Cost Effectiveness of Endoscopic Cordectomy Using Microdissection Electrodes with Laser Cordectomy and Radiotherapy - OYSU, ÇAĞATAY (GALENOS YAYINCILIK, 2019)
Objective: To compare the acoustic parameters and the cost effectiveness achieved after endoscopic cordectomy using radiofrequency microdissection electrodes (ECRM) with those of transoral laser cordectomy and radiotherapy. Methods: The study included 81 disease-free patients previously treated for early larynx carcinoma (30 with ECRM, 27 with transoral laser cordectomy, 24 with primary radiotherapy). Post-treatment voice analysis was performed in all patients. Additionally, the cost effectiveness of all treatment procedures was calculated. Results: The GRBAS (G: Grade, R: Roughness, B: Breathiness, A: Asthenia, and S: Strain) scale showed a significant difference between the groups (p<0.001). The mean values for perceptive assessment score in the radiotherapy group were significantly lower than those in the ECRM group (p<0.05). There were no significant differences between the ECRM group and the transoral laser cordectomy group in terms of the perceptive assessment scores (p>0.05 for all). Percent jitter, percent shimmer and fundamental frequency (F0) were significantly different in the radiotherapy group than the ECRM and the transoral laser cordectomy groups (p<0.05). Maximum phonation time (MPT) in the radiotherapy group was significantly longer than the ECRM and transoral laser cordectomy groups (p<0.001). There were no significant differences between the ECRM group and the transoral laser cordectomy group in terms of the MPT (p>0.05). The mean cost of the ECRM technique was statistically lower than the other treatment techniques (p<0.05). Moreover, the length of hospital stay after ECRM was statistically significantly shorter than was after laser cordectomy (p<0.05). Conclusion: Objective and perceptive voice analysis after ECRM showed comparable results with transoral laser cordectomy, but poorer results than radiotherapy. Cost effectiveness of ECRM was found to be better than the other two treatment techniques.
Keywords: Early laryngeal cancer; voice quality; radiofrequency ablation; cost effectiveness; GLOTTIC CARCINOMA; SURGERY; CANCER; RADIATION; OUTCOMES